Investigation of sudden electron density depletions observed in the dusk sector by the Poker Flat, Alaska incoherent scatter radar in summer. Issue 12 (20th December 2014) - Richards, P. G.; Nicolls, M. J.; St.‐Maurice, J.‐P.; Goodwin, L.; Ruohoniemi, J. M.
Abstract: This paper investigates unusually deep and sudden electron density depletions (troughs) observed in the Poker Flat (Alaska) Incoherent Scatter Radar data in middle summer of 2007 and 2008. The troughs were observed in the premidnight sector during periods of weak magnetic and solar activity. The density recovered to normal levels around midnight. At the time when the electron density was undergoing its steep decrease, there was usually a surge of the order of 100 to 400 K in the ion temperature that lasted less than 1 h. The Ti surges were usually related to similar surges in the AE index, indicating that the high‐latitude convection pattern was expanding and intensifying at the time of the steep electron density drop. The convection patterns from the Super Dual Auroral Radar Network also indicate that the density troughs were associated with the expansion of the convection pattern to Poker Flat. The sudden decreases in the electron density are difficult to explain in summer because the high‐latitude region remains sunlit for most of the day. This paper suggests that the summer density troughs result from lower latitude plasma that had initially been corotating in darkness for several hours post sunset and brought back toward the sunlit side as the convection pattern expanded. The magnetic declination of ~22° east at 300 km at Poker Flat greatly facilitates the contrast between the plasma convecting from lower latitudes and the plasma that follows the high‐latitude convection pattern. Key Points: Modeling premidnight plasma density troughs observed in Alaska in summer Density troughs occur during weak solar and magnetic activity Model indicates cause is convection of low‐density plasma from lower latitudes